2020
DOI: 10.1186/s43055-020-00278-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of congenital anomalies of genito-urinary system on fetal magnetic resonance imaging

Abstract: Background: The aim of this study is to elucidate the spectrum of commonly encountered anomalies affecting fetal genito-urinary system (GUS) on fetal MRI and examine its utility in providing better morphological information resulting in improved diagnostic accuracy and in detecting additional malformations. The study also aims to highlight the promising role of fetal MRI in the detection and characterization of renal fusion anomalies like the horseshoe kidney or developmental abnormalities such as renal agenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Only about one-fifth of the patients in the present study had a prenatal diagnosis of their pathology. However, Gupta et al reported that genitourinary anomalies comprise 30-50% of all anomalies detected on prenatal scan [30].…”
Section: Discussionmentioning
confidence: 99%
“…Only about one-fifth of the patients in the present study had a prenatal diagnosis of their pathology. However, Gupta et al reported that genitourinary anomalies comprise 30-50% of all anomalies detected on prenatal scan [30].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal urogenital anomalies comprise 30%-50% of all abnormalities diagnosed prenatally or at birth. 1 They encompass a wide spectrum of abnormalities from mild forms of simple pyelectasis to severe, lifeincompatible forms of bilateral renal agenesis that may lead to pulmonary hypoplasia. 2 Based on the type of the anomalies, there is a wide variety of subgroups: (a) renal ectopia, (b) renal agenesis, (c) abnormal renal size malformation, (d) obstructive diseases, (e) cystic diseases, (f) tumoral lesions, and (g) miscellaneous anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal urogenital anomalies comprise 30%–50% of all abnormalities diagnosed prenatally or at birth 1 . They encompass a wide spectrum of abnormalities from mild forms of simple pyelectasis to severe, life‐incompatible forms of bilateral renal agenesis that may lead to pulmonary hypoplasia 2 .…”
Section: Introductionmentioning
confidence: 99%